2021
DOI: 10.3390/surgeries2020022
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Integrative Medicine Recommendations for Patients with Pancreatic Cancer

Abstract: Introduction: Integrative medicine (IM) is a relatively new field where non-traditional therapies with peer-reviewed evidence are incorporated or integrated with more traditional approaches. Methods: A systematic review of the literature from the last 10 years was done by searching clinical trials and randomized-controlled trials on Pubmed that discuss nutrition, supplementation, and lifestyle changes associated with “Pancreatic Cancer.” Results: Only 50 articles ultimately met the inclusion criteria for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Moreover, not only fried food adversely affect the CVS system, but it also contributes to cancer development 28 . Evidence indicates an increased likelihood of developing chronic diseases, including hypertension with a higher frequency of consuming fried foods, specifically at a rate of four or more times every week 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, not only fried food adversely affect the CVS system, but it also contributes to cancer development 28 . Evidence indicates an increased likelihood of developing chronic diseases, including hypertension with a higher frequency of consuming fried foods, specifically at a rate of four or more times every week 8 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, not only fried food adversely affect the CVS system, but it also contributes to cancer development. 28 Evidence indicates an increased likelihood of developing chronic diseases, including hypertension with a higher frequency of consuming fried foods, specifically at a rate of four or more times every week. 8 Cooking food through frying leads to an oxidation process that raises the presence of trans-fatty acids in the food, which in turn correlates with an elevated risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The bowel should be inspected for oedema as well as other associated anomalies, then the role of different treatment strategies should be considered. Postoperative care and nutritional support is very crucial [15] . Even though science is advocating for gastroschisis repair using umbilical cord graft for its impressive end results, we should note that the developing umbilical hernia is not to be taken lightly as its surgical repair is done with caution due to bowel adhesions to anterior abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified several loci of interest associated with T2D in pediatrics, including loci within free fatty acid receptor‐1 ( FFAR1 ), upstream transcription factor‐2 ( USF2 ), and tumor necrosis factor‐related protein‐9 ( C1QTNF9 ) 4 . Studies have shown that the epigenome is an essential target for age‐related physiological changes, as it is modifiable by the environment 5 . Thus, it is considered a significant potential contributor to the incidence of T2D in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…4 Studies have shown that the epigenome is an essential target for age-related physiological changes, as it is modifiable by the environment. 5 Thus, it is considered a significant potential contributor to the incidence of T2D in adolescents. Relatively little is known about epigenetic age in adolescents with T2D.…”
mentioning
confidence: 99%